THE EFFECT OF N-METHYL-d-ASPARTATE RECEPTOR BLOCKADE ON ACETYLCHOLINE EFFLUX IN THE DORSOMEDIAL STRIATUM DURING RESPONSE REVERSAL LEARNING - Palencia, C. A. (2006)
Separate experiments found that activation of N-methyl-d-aspartate (NMDA) receptors or increased acetylcholine (ACh) efflux in the rat dorsomedial striatum is critical for learning when conditions require a shift in strategies. Increasing evidence indicates that NMDA receptor activity affects cholinergic efflux in the basal ganglia. The present studies determined whether NMDA receptor blockade in the dorsomedial striatum with dl-2-amino-5-phosphonopentanoic acid (AP-5) affects dorsomedial striatal ACh output in a resting condition, as well as during response reversal learning. Experiment 1 investigated the effects of AP-5 (12.5, 25 or 50 µM) infused into the dorsomedial striatum on ACh output in a resting condition. AP-5 infusion at 25 and 50 µM led to a 20% and 40% decrease in dorsomedial striatal ACh output, respectively. AP-5 (12.5 µM) infusion did not change dorsomedial striatal ACh output from basal levels. Experiment 2 determined whether dorsomedial striatal ACh efflux increases during response reversal learning and whether AP-5, at a dose that does not affect basal levels, modifies response reversal learning and ACh efflux. Following acquisition of a response discrimination, rats had microdialysis probes bilaterally inserted into the dorsomedial striatum prior to the reversal learning test. After baseline samples, rats received a response reversal learning test for 30 min. Control rats rapidly improved in the reversal learning session while simultaneously exhibiting an approximately 40% increase in ACh output compared with baseline levels. AP-5 (12.5 µM) treatment during testing significantly impaired response reversal learning while concomitantly blocking an increase in ACh output. These findings suggest that NMDA receptor activation in the dorsomedial striatum may facilitate a shift in response patterns, in part, by increasing ACh efflux.